(untitled) (Journal of Music Research Online, 2022)
The inner gatherings of the music manuscript Modena, Biblioteca Estense, MS. α.M.5.24 (Mod AII-IV) contain a tangle of politically-charged songs, mostly in French, referring to the tumultuous Great Schism of the Western Church (1378–1417) and the prowess of several princes of ascendant Italian states during the same period. Some scholars have connected the repertoire of Mod AII-IV with Pétros Fílargos, sometime Archbishop of Milan and then the short-lived conciliar pope Alexander V. Yet art-historical evidence now strongly suggests that Mod AII-IV was completed during the pontificate of Alexander’s successor, John XXIII, between September 1410 and March 1411 in Bologna. During the first two years of John’s pontificate the influential and wealthy prince of France, Louis II of Anjou, prosecuted his claim for title of the Kingdom of Naples in Italy, simultaneously supporting John XXIII’s military campaign to reclaim Rome. This article explores a new hypothesis that part of the repertoire of Mod AII-IV—and possibly the manuscript’s very structure—reflects the presence of the Angevin prince at the court of John XXIII in Bologna in the second half of 1410. It considers how other political threads running through this manuscript render it an unlikely candidate for a source connected with the pro-Visconti Alexander V.